Functional Investigation of a Neuronal Microcircuit in the CA1 Area of the Hippocampus Reveals Synaptic Dysfunction in Dravet Syndrome Mice - Almog, Yael; Mavashov, Anat; Brusel, Marina; Rubinstein, Moran (Frontiers in Molecular Neuroscience, 2022)
Dravet syndrome is severe childhood-onset epilepsy, caused by loss of function mutations in the SCN1A gene, encoding for the voltage-gated sodium channel NaV1.1. The leading hypothesis is that Dravet is caused by selective reduction in the excitability of inhibitory neurons, due to hampered activity of NaV1.1 channels in these cells. However, these initial neuronal changes can lead to further network alterations. Here, focusing on the CA1 microcircuit in hippocampal brain slices of Dravet syndrome (DS, Scn1aA1783V/WT) and wild-type (WT) mice, we examined the functional response to the application of Hm1a, a specific NaV1.1 activator, in CA1 stratum-oriens (SO) interneurons and CA1 pyramidal excitatory neurons. DS SO interneurons demonstrated reduced firing and depolarized threshold for action potential (AP), indicating impaired activity. Nevertheless, Hm1a induced a similar AP threshold hyperpolarization in WT and DS interneurons. Conversely, a smaller effect of Hm1a was observed in CA1 pyramidal neurons of DS mice. In these excitatory cells, Hm1a application resulted in WT-specific AP threshold hyperpolarization and increased firing probability, with no effect on DS neurons. Additionally, when the firing of SO interneurons was triggered by CA3 stimulation and relayed via activation of CA1 excitatory neurons, the firing probability was similar in WT and DS interneurons, also featuring a comparable increase in the firing probability following Hm1a application. Interestingly, a similar functional response to Hm1a was observed in a second DS mouse model, harboring the nonsense Scn1aR613X mutation. Furthermore, we show homeostatic synaptic alterations in both CA1 pyramidal neurons and SO interneurons, consistent with reduced excitation and inhibition onto CA1 pyramidal neurons and increased release probability in the CA1-SO synapse. Together, these results suggest global neuronal alterations within the CA1 microcircuit extending beyond the direct impact of NaV1.1 dysfunction.